Modulation of microRNA processing by 5‐lipoxygenase. Issue 2 (17th November 2020) - Uebbing, Stella; Kreiß, Marius; Scholl, Friederike; Häfner, Ann‐Kathrin; Sürün, Duran; Garscha, Ulrike; Werz, Oliver; Basavarajappa, Devaraj; Samuelsson, Bengt; Rådmark, Olof; Suess, Beatrix; Steinhilber, Dieter
Abstract: The miRNA biogenesis is tightly regulated to avoid dysfunction and consequent disease development. Here, we describe modulation of miRNA processing as a novel noncanonical function of the 5‐lipoxygenase (5‐LO) enzyme in monocytic cells. In differentiated Mono Mac 6 (MM6) cells, we found an in situ interaction of 5‐LO with Dicer, a key enzyme in miRNA biogenesis. RNA sequencing of small noncoding RNAs revealed a functional impact, knockout of 5‐LO altered the expression profile of several miRNAs. Effects of 5‐LO could be observed at two levels. qPCR analyses thus indicated that (a) 5‐LO promotes the transcription of the evolutionarily conserved miR‐99b/let‐7e/miR‐125a cluster and (b) the 5‐LO‐Dicer interaction downregulates the processing of pre‐let‐7e, resulting in an increase in miR‐125a and miR‐99b levels by 5‐LO without concomitant changes in let‐7e levels in differentiated MM6 cells. Our observations suggest that 5‐LO regulates the miRNA profile by modulating the Dicer‐mediated processing of distinct pre‐miRNAs. 5‐LO inhibits the formation of let‐7e which is a well‐known inducer of cell differentiation, but promotes the generation of miR‐99b and miR‐125a known to induce cell proliferation and the maintenance of leukemic stem cell functions.